2019
DOI: 10.9734/jeai/2019/v33i330146
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Biomass Quantification in Eucalyptus saligna Smith Stand at the End Rotation in the South of Brazil

Abstract: The quantification of wood stock and other components of biomass is fundamental for forest planning. Given the difficulty of obtaining these data, the present study aims at the formulation of equations and the estimation of the different components of biomass, volume with and without bark, form factor and height of the trees at the end rotation. The study was carried out in the municipality of São Gabriel state of Rio Grande do Sul, Brazil with Eucalyptus saligna 10-year-old. The experimental design of the inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…While in the present study the lowest adjustment was for the bark component R² aj 0.74, Viera et al [23] show that the lowest adjustment occurred for the leaves 0.86. For Momolli et al [26] the adjustments were much higher than the other authors, being the smallest adjustment for height with R² aj of 0.97.…”
Section: Biomass Modelingmentioning
confidence: 65%
See 3 more Smart Citations
“…While in the present study the lowest adjustment was for the bark component R² aj 0.74, Viera et al [23] show that the lowest adjustment occurred for the leaves 0.86. For Momolli et al [26] the adjustments were much higher than the other authors, being the smallest adjustment for height with R² aj of 0.97.…”
Section: Biomass Modelingmentioning
confidence: 65%
“…However, that the best adjustments were for the variables wood, total and height. Momolli et al [26] also observed greater variability of the residues for the branches, leaves and bark components.…”
Section: Biomass Modelingmentioning
confidence: 92%
See 2 more Smart Citations
“…The modeling of above-ground biomass in a 10 years old clone of Eucalyptus saligna stand was performed by Momolli et al [20]. The authors found 89; 5.9; 3.2 and 1.8% of the biomass in the wood, bark, branch and leaf respectively.…”
Section: Soil Fertilitymentioning
confidence: 99%